Do Entrepreneurial Motivation, Personality, and Social Networking Improve Financial Access in India? - Singh, Sheetal; Basri, Savitha (Prabandhan: Indian Journal of Management, 2025)
Purpose : Social networking has had an immense influence on entrepreneurial success. The present study examined the mediating effect of social networking on the associations between motivation and personality factors, as well as financial access among startups in India. Methodology : A cross-sectional quantitative survey was conducted in the Bangalore and Delhi NCR regions of India to collect data from 376 entrepreneurs. The data were analyzed via SmartPLS 4 software. Findings : The results indicated that social networking had a substantial influence on financial access in entrepreneurial startups. Personality traits, such as neuroticism, had a direct effect on social networking and financial access. Social networking mediated the relationship between neuroticism and access to finance. Practical Implications : Entrepreneurs should improve their social networking ties and connections and leverage them strategically to obtain more funds. Originality : This study examined the combined effects of the motivational and personality factors of entrepreneurs, which is unique to social networking and financial access in start-ups. It contributes new knowledge to the entrepreneurial literature, especially in the Indian context.